Comparing older people's drinking habits in four Nordic countries: Summary of the thematic issue. Issue 5 (October 2020) - Tigerstedt, Christoffer; Agahi, Neda; K Bye, Elin; Ekholm, Ola; Härkönen, Janne; Jensen, Heidi Rosendahl; Lau, Cathrine Juel; Makela, Pia; Moan, Inger Synnøve; Parikka, Suvi; Raninen, Jonas; Vilkko, Anni; et al.
Aim: The present article summarises status and trends in the 21st century in older people's (60–79 years) drinking behaviour in Denmark, Finland, Norway and Sweden and concludes this thematic issue. Each country provided a detailed report analysing four indicators of alcohol use: the prevalence of alcohol consumers, the prevalence of frequent use, typical amounts of use, and the prevalence of heavy episodic drinking (HED). The specific aim of this article is to compare the results of the country reports. Findings: Older people's drinking became more common first in Denmark in the 1970s and then in the other countries by the 1980s. Since 2000 the picture is mixed. Denmark showed decreases in drinking frequency, typically consumed amounts and HED, while in Sweden upward trends were dominant regarding prevalence of consumers and frequency of drinking as well as HED. Finland and Norway displayed both stable indicators except for drinking frequency and proportion of women consumers where trends increased. In all four countries, the gender gap diminished with regard to prevalence and frequency of drinking, but remained stable in regard to consuming large amounts. In Norway the share of alcohol consumers among women aged 60–69 years exceeded the share among men. During the late 2010s, Denmark had the highest prevalence of alcohol consumers as well as the highest proportion drinking at a higher frequency. Next in ranking was Finland, followed by Sweden and Norway. This overall rank ordering was observed for both men and women. Conclusion: As the populations aged 60 years and older in the Nordic countries continue to grow, explanations for the drivers and consequences of changes in older people's drinking will become an increasingly relevant topic for future research. Importantly, people aged 80 years and older should also be included as an integral part of that research.